2022
DOI: 10.1002/rcs.2445
|View full text |Cite
|
Sign up to set email alerts
|

Multiple instance convolutional neural network for gallbladder assessment from laparoscopic images

Abstract: Background We present an artificial intelligence framework for vascularity classification of the gallbladder (GB) wall from intraoperative images of laparoscopic cholecystectomy (LC). Methods A two‐stage Multiple Instance Convolutional Neural Network is proposed. First, a convolutional autoencoder is trained to extract feature representations from 4585 patches of GB images. The second model includes a multi‐instance encoder that fetches random patches from a GB region and outputs an equal number of embeddings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Although this type of information was not available in the dataset, it may well be used as an additional input in the RSD pipeline. For example, prior studies have shown that important information about the GB condition, which is related to the operation complexity, may well be extracted from still images captured during the operation 32 . In the future, we aim to fuse the proposed model with such intraoperative indicators and preoperative data to improve RSD prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Although this type of information was not available in the dataset, it may well be used as an additional input in the RSD pipeline. For example, prior studies have shown that important information about the GB condition, which is related to the operation complexity, may well be extracted from still images captured during the operation 32 . In the future, we aim to fuse the proposed model with such intraoperative indicators and preoperative data to improve RSD prediction.…”
Section: Discussionmentioning
confidence: 99%